(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The article intends to carry out a critical analysis in relation to the current phase of society, influenced by a process of neoliberal globalization, where public spaces are increasingly being replaced by private spaces and those that exist tend to be more and more elite, increasing the power of the strongest and weakening the dispossessed. It seeks to question whether it is possible to speak of Democratic State according to the rule of the majority, demonstrated through the study of culture and politics the need and importance of education in rights with an emphasis on citizenship. The deductive method will be used. Keywords: Globalization. Democratic State. Culture. Policy. Citizenship.